Rosario+Vampire. 07, Exorcist - Ikeda, Akihisa, 1976- (Viz Media, 2009)
Who's going to win in a school when the battle isn't between jocks and nerds but between vampires and werewolves? In this episode, Moka is trying to kill Tsukune ... but only because she's being controlled by Mako Yakumaru, one of the revenge-seeking monstrels (mixed breed monsters who hate purebred monsters).